Critique to the contemporaneous cynic reason: life and learning relationship review. (2013)
In the present article it is proposed to think about life and learning relationship from the turn produced by the introduction of the cynical reason in the contemporaneous societies. Three stages form this writing. In the first one, the ways of functioning of the critique to the cynical reason, from Sloterdjik and Deleuze, are contextualized. In the second one, the implications of such cynical reason, designated by Sloterdjik as reversion of the life’s effects on the learning and their relationship are discussed. And in the third one, the Jacotot’s experience, reconstructed by Jaques Ranciere, is picked up in order to give other senses and understandings to today’s life-learning relationship.